Electrochemical Synthesis of Silver Nanoparticles in the Presence of Poly(N-vinylpyrrolidone) and the Study of Phase-Transfer - Li, Qiuhong (Asian Journal of Chemistry, 2010)
Poly(N-vinylpyrrolidone)-protected spherical shape silver nano-particles with diameter about 30-100 nm were prepared by electrochemical method using the rotating glassy carbon as working electrode. The result showed that the electrode rotation rate had a great effect on the silver colloids. UV-Vis absorption spectra, X-ray diffraction and scanning electron microscopy (SEM) were employed to characterize the silver nanoparticles. Moreover, based on the decrease of the solubility of poly(N-vinylpyrrolidone) in water with the temperature increase, the obtained silver nanoparticles were transferred from aqueous phase to organic phase successfully by phasetransfer method, which improved the catalytic activity of silver nanoparticles.